Living Hadith in the Slametan Tradition in Javanese Society: A Qualitative Study of the Interpretation of Hadith in Local Culture - Hafid Yusuf Hidayatulloh; Nasrulloh Nasrulloh (Penerbit Hellow Pustaka, 2026)
Slametan is understood not simply as a social ritual, but as a symbolic space where the values ​​of the Prophet Muhammad's hadith are revived and reinterpreted within the Javanese cultural context. This study aims to understand the phenomenon of Living Hadith in the Javanese slametan tradition. Living Hadith is a form of actualization of the values ​​of the Prophet Muhammad's hadith within the local cultural context, highlighting how the hadith text is practiced and internalized in the social life of the community. The slametan tradition, as a religious expression of the Javanese community, reflects the internalization of Islamic values ​​through contextual interpretations rich in social and spiritual meaning. This study uses a qualitative phenomenological approach with participatory observation, in-depth interviews, and documentation. The results show that the interpretation of hadith by the Javanese community is contextual and symbolic, not merely textual. The slametan tradition serves as a means to strengthen social solidarity, express gratitude, and demonstrate love for the Prophet Muhammad. Through this tradition, Javanese society affirms its religious identity in an inclusive and harmonious manner. These findings enrich the contextual study of hadith and broaden understanding of the dynamic relationship between religion and culture in the Indonesian archipelago.